Upaya Perlindungan terhadap Anak Korban Penganiayaan Sesama Anak Sekolah - Patrisia Jihan S. Pido; Suwitno Y. Imran; Julisa Aprilia Kaluku (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to discuss efforts to protect children who are victims of abuse by fellow school children. This research uses empirical legal methods and is based on phenomena and realities in the field, then analyzed descriptively qualitatively. The results of the research show that the Gorontalo Regional Police's efforts to protect victims of abuse of fellow school children include providing security for perpetrators of abuse by the police when they receive information from the victim's parents or the school regarding allegations of child abuse in the school environment. The police followed up by sending officers to check and arrest the perpetrators; Carrying out examinations in a family atmosphere and fulfilling the victims' rights during the legal process; and Ensure that victims receive compensation, where a victim is entitled to compensation, as well as medical rehabilitation and recovery for the physical and psychological suffering they have experienced. In several cases of abuse, the perpetrator paid for the losses suffered by the victim, especially material compensation in the form of compensation payments due to the victim's physical, mental and psychological losses during the recovery and rehabilitation process. The perpetrator paid all the compensation suffered by the victim, using assets belonging to the perpetrator's family, especially hospital treatment costs.